Protection from domestic violence in the Republic of Kosovo - Kosumi, Ibrahim (Technium Social Sciences Journal, 2021)
The paper analyzes and elaborates the protection from domestic violence, the subjects protected by law, the protection measures provided by law such as: lawsuit, court order, shelter of the victim, issuance of protection order, investigation, identification and responsibilities of the police on the basis of the law on the protection of victims of domestic violence. The paper will also analyze the measures taken to prevent domestic violence, strategies and efforts. Mutual police communications with the public through press releases, leaflets, leaflets, targeting negative phenomena in society, transparency on all taboo topics in the public interest but understood on the basis of legal restrictions. The paper also included research by various authors from both national and international perspectives on domestic violence. The paper uses inductive and deductive research methods, as well as analytical and comparative methods. This paper contributes to the existing scientific literature, especially the legal, criminological and victimological literature. Furthermore, this paper is likely to contribute to the work of NGOs that deal with providing victims of domestic violence, but also to the work of state bodies for the prevention of domestic violence, which is and remains a national challenge.